Recent Advances in Aging and Immunosenescence: Mechanisms and Therapeutic Strategies - Shuaiqi Wang; Tong Huo; Mingyang Lu; Yueqi Zhao; Jianmin Zhang; Wei He; Hui Chen (Cells)
Cellular senescence is an irreversible state of cell cycle arrest. Senescent cells (SCs) accumulate in the body with age and secrete harmful substances known as the senescence-associated secretory phenotype (SASP), causing chronic inflammation; at the same time, chronic inflammation leads to a decrease in immune system function, known as immunosenescence, which further accelerates the aging process. Cellular senescence and immunosenescence are closely related to a variety of chronic diseases, including cardiovascular diseases, metabolic disorders, autoimmune diseases, and neurodegenerative diseases. Studying the mechanisms of cellular senescence and immunosenescence and developing targeted interventions are crucial for improving the immune function and quality of life of elderly people. Here, we review a series of recent studies focusing on the molecular mechanisms of cellular senescence and immunosenescence, the regulation of aging by the immune system, and the latest advances in basic and clinical research on senolytics. We summarize the cellular and animal models related to aging research, as well as the mechanisms, strategies, and future directions of aging interventions from an immunological perspective, with the hope of laying the foundation for developing novel and practical anti-aging therapies.